PENGGUNAAN REALISTIC MATHEMATIS EDUCATION (RME) SEBAGAI HASIL BELAJAR MATEMATIKA MATERI PECAHAN SEDERHANA DI ABAD 21 - Kunti Dian Ayu Afiani; Aurellia Faradita Putri (Universitas Muhammadiyah Surabaya, 2022)
Teachers have a very important role in the success of learning in the classroom. This requires teachers to modify the use of learning methods, media, strategies, attitudes and characteristics of teachers in managing teaching and learning activities. This research can improve mathematical performance, especially in simple fractions. the benefits of using the Real Math Teaching (RMT) learning model in students' mathematics learning achievement. At the age of cognitive development, elementary school students are always interested in objects that can be captured by their five senses. In abstract mathematics, students need aids in the form of aids and teaching aids that can clarify what the teacher is saying. Students can understand it faster. The research was conducted at SDN Rangkah I, the number of students was 35 people consisting of 20 female students and 15 male students. The method used by the researcher is classroom action research. The process of collecting data is done through the method of observation and testing. The implementation of this research took place in two cycles. The results obtained from the action in the first cycle an average of 71,4 % increased to 100% in the second cycle.Â Keywords: Learning Outcomes, Realistic Mathematics Education (RME), Simple Fraction